PUPILS' ATTITUDES TOWARDS THE SUBJECT OF TECHNOLOGY AS A FACTOR INFLUENCING THE CHOICE OF SECONDARY SCHOOL - LUKACOVA, Danka; BANESZ, Gabriel; STETKOVA, Adriana (Journal of Technology and Information Education, 2024)
The present work is aimed at finding out the attitude of 15-year-old pupils towards the subject of Technology and their general attitude towards technical education. In the research, we focused on finding the difference in the attitudes of the pupils towards the subject of Technology in relation to their choice of secondary school or the gender of the pupil. In the research, we used a questionnaire for pupils. The questionnaire is a translation of the 'Pre-inspection survey: pupils (secondary)', recommended to schools by the Welsh Inspectorate. We subjected the data collected to quantitative and qualitative analysis. The Mann-Whitney U-test was used to investigate differences in pupils' attitudes towards the subject of Technology in relation to their choice of secondary school or the gender of the pupil. We found that the difference in 15-year-old pupils' attitudes towards technical education is statistically significant between the group of pupils applying to vocational secondary schools and the group of pupils applying to grammar schools. Pupils who have a positive attitude towards the subject of Technology apply to secondary vocational schools. Further, we find that the difference in the attitudes of 15-year-old pupils towards technical education is statistically significant between girls and boys. Boys showed more positive attitudes towards the subject of Technology than girls in their responses.Predlozena praca je zamerana na zistovanie vztahu 15-rocnych ziakov k predmetu technika a ich celkovy postoj k technickemu vzdelavaniu. Vo vyskume sme sa zamerali na hladanie rozdielu v postojoch ziakov k predmetu technika v suvislosti s ich volbou strednej skoly, resp. pohlavim ziaka. Vo vyskume sme pouzili dotaznik pre ziakov. Dotaznik je prekladom ``Pre-inspection survey: pupils (secondary)'', odporucany skolam waleskou inspekciou. Ziskane udaje sme podrobili kvantitativnej a kvalitativnej analyze. Na zistenie rozdielov v postojoch ziakov k predmetu technika v suvislosti s ich volbou strednej skoly, resp. pohlavim ziaka sme pouzili Mann-Whitney U-test. Zistili sme, ze rozdiel v postojoch 15-rocnych ziakov k technickemu vzdelavaniu je statisticky vyznamny medzi skupinou ziakov, ktori sa hlasia na stredne odborne skoly a skupinou ziakov, ktori sa hlasia na gymnazia. Na stredne odborne skoly sa hlasia ziaci, ktori maju pozitivny vztah k predmetu technika. Dalej sme zistili, ze rozdiel v postojoch 15-rocnych ziakov k technickemu vzdelavaniu je statisticky vyznamny medzi dievcatami a chlapcami. Chlapci prejavili v odpovediach pozitivnejsi postoj k predmetu technika ako dievcata.
Keywords: subject technology; pupils' attitudes; choice of secondary school.predmet technika; postoje ziakov; volba strednej skoly.